1988
DOI: 10.1002/actp.1988.010390816
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von aromatischen Polyketonen durch Fällungspolykondensation

Abstract: Aromatische Polyketone wurden durch Fällungspolykondensation aus den Säurechloriden der Iso‐ und Terephthalsäure, des 3,3‐Bis(4′‐carboxy‐phenyl)phthalids, des Bis(4‐carboxy‐phenyl)ethers jeweils mit Diphenylether sowie direkt aus 4‐Phenoxybenzoylchlorid hergestellt. Der Einifluß von Katalysator, Lösungsmittel und Temperatur auf den Syntheseverlauf wurde untersucht und die Struktur der erhaltenen Polyketone aufgeklärt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Because the carbonyl groups of the reactants and the reaction products are complexed with AlCl 3 , and thereby deactivate it, AlCl 3 is generally employed at more than one equivalent of carbonyl groups in the reaction medium . The optimum molar ratio of AlCl 3 to carbonyl group was reported to be 1.35 to 1.45 . In our modified Friedel‐Crafts acylation polycondensation reaction, an additional amount of AlCl 3 was needed for the formation of a 1:1 complex of AlCl 3 and NMP due to the addition of NMP as the controlling agent.…”
Section: Resultsmentioning
confidence: 97%
“…Because the carbonyl groups of the reactants and the reaction products are complexed with AlCl 3 , and thereby deactivate it, AlCl 3 is generally employed at more than one equivalent of carbonyl groups in the reaction medium . The optimum molar ratio of AlCl 3 to carbonyl group was reported to be 1.35 to 1.45 . In our modified Friedel‐Crafts acylation polycondensation reaction, an additional amount of AlCl 3 was needed for the formation of a 1:1 complex of AlCl 3 and NMP due to the addition of NMP as the controlling agent.…”
Section: Resultsmentioning
confidence: 97%
“…after phase separation. Recently we have [6][7][8][9][10] shown that precipitation electrophilic Friedel Crafts polycondensation can be performed in such a way that the polymer precipitate presents quite uniform small particles. This process has unquestionable technological advantages, since pure polymer can be recovered just by filtration followed by washing with organic solvents and drying.…”
Section: Introductionmentioning
confidence: 99%
“…Because the carbonyl groups of the reactants and the reaction products are complexed with AlCl 3 , and thereby deactivate it, AlCl 3 is generally employed at more than one equivalent of carbonyl groups in the reaction medium 30, 31. The optimum ratio of AlCl 3 to carbonyl group was reported to be 1.35–1.45 13, 32. In our modified Friedel–Crafts acylation polycondensation, an additional amount of AlCl 3 was needed for the formation of a 1:1 complex of AlCl 3 and NMP due to the addition of Lewis base (NMP) as the controlling agent.…”
Section: Resultsmentioning
confidence: 99%